Analysing the Social Skills and Problem Behavior of the Immigrant Learners - Toro, Cherry Rosa Di; Revalde, Helen; Pinili, Lilibeth; Añero, Marjorie (International Journal of Educational Studies, 2025)
This research analysed the social skills and problem behavior of immigrant learners inside the classroom at L’enfant Roi Montessori Kindergarten. This study utilized a descriptive correlational design. It utilized an adopted survey questionnaire instrument. It was conducted at L’enfant Roi Montessori Kindergarten School, Elementary Department, located in Kirchberg Luxembourg. The respondents were 84 parents and 16 teachers, purposively selected, of the learners enrolled in kindergarten, who gave their analysation as to the social skills and problem behavior of the immigrant learners. The parent respondents were analysed in terms of the number of siblings, country of origin, educational attainment. The teacher respondent analysed the social skills and problem behavior of the immigrant learners. The data gathered were statistically treated using frequency count, simple percentage, weighted mean, and Pearson Correlation Coefficient (r). Findings revealed that the teacher’s respondent analysed the social skills to the immigrant learners inside the classroom as 3.00, suggests that these issues have significantly happened sometimes. The teacher’s respondent analysed the problem behavior to the immigrant learners inside the classroom as 2.46 suggests that these issues have rarely occurred to immigrant learners. There was a low positive correlation was found on the impact of social skills and problem behaviour on immigrant learners. This is hard to find constant dynamic nature of educational strategies highlights the need for ongoing adaptation to the varying needs and challenges encountered by learners. It is concluded that there were no relationship of social skills and problem behaviour were varied between the number of siblings, origin; and the education attainment of the parents, regarding the interventions in family, and teacher, highlighting the need to improved language course for learners and parent or after school program to better cope up the problem of immigrant in the new country. It is recommended that should be adopted to establish stronger communication channels between teachers and parents to address he educational challenges and formulate better and consistent interventions.